Rural-Urban Female Migration in Bangladesh: Need for Information Support and Institutional Responses (Global Journal of Human-Social Science, 2013)
This paper portrays lives and livelihoods scenario of female associated with ruralurban migration in Bangladesh. The techniques deplored are the interview and Focus Group Discussion (FGD) methods in collecting data. Internal migration of female has been increased with complexity. This micro level study finds that possible female migrants are enticed, in many cases, with promises of a better life and dream in cities due to lack of information. They are deprived from rights and entitlements; whatever engaged in formal or informal employment. But evidence pointing that voice of female workers is comparatively loud where protection framework exists. This paper urges to take collaborative initiative by stakeholders for developing and disseminating standardized information. Information will help female migrants to be informed and decision making. In concluding this paper, it is recommended that the Government of Bangladesh (GoB) should develop a comprehensive national policy immediately on rural-urban migration; and gradually include informal employment under protection framework.
Keywords: female; information; migration; protection framework; rights; well-beings